Investigating the effect of El-nino and La-nina on precipitation in the coastal belts of Ghana - Kwao, John Einstein Kojo (University of Cape Coast, 2022)
The research is carried out to investigate the effect of El Nino and La Nina events of oceans and seas on the rainfall of the coastal belts of Ghana. The study is done by analysing the global Oceanic Nino Indices (ONI) and the Southern Oscillation Indices (SOI) over a thirty-year period. The result of these global indices are then compared to the annual mean rainfall for five different major coastal towns in Ghana. The five towns used for the research include Accra, Tema, Ada, Saltpond and Takoradi for the period 1986 to 2015. The data were analysed using Microsoft Excel and Statistical Package for Social Sciences (SPSS). The annual rainfall values for thirty-years in each of the five major coastal towns of Ghana and the global indices are used to identify the El Nino and La Nina years over the thirty-year climatological period. The effect of ONI and SOI values of the coast on mean annual and monthly rainfall are determined using Microsoft Excel and R-program to plot graphs. The analysis showed that the El Nino Southern Oscillation (ENSO) events contribute to a variation of rainfall in the coastal sectors of Ghana. The effect of El Nino Southern Oscillations events on the rainfall along the coastal belts of Ghana do not provide a consistent trend for accurate prediction. It was however noted in the research that all five study stations recorded a slightly higher amount of both monthly and annual rainfall during the La Nina regimes.
xxi, 129p:,ill.
Keywords: El Nino; La Nina; Oceanic Nino Index; Rainfall; Southern Oscillation Index; Walker circulation